Defining the boundary of the plate, backed by two rectangular ribs - Доник, Т.В. (Proceedings of National Aviation University (archive), 2007)
The problem about a limited condition of a plate supported is considered by two rectangular edges. Influence of edges on intense-deformed and a limiting condition of a plate is investigated.